A Radical Process towards the Development of Transition‐Metal‐Free Aromatic CarbonCarbon Bond‐Forming Reactions. Issue 47 (25th October 2013) - Chan, Tek Long; Wu, Yinuo; Choy, Pui Ying; Kwong, Fuk Yee
Abstract Transition‐metal‐free cross‐coupling reactions have been a hot topic in recent years. With the aid of a radical initiator, a number of unactivated arene CH bonds can be directly arylated/functionalized by using aryl halides through homolytic aromatic substitution. Commercially available or specially designed promoters (e.g. diamines, diols, and amino alcohols) have been used to make this synthetically attractive method viable. This protocol offers an inexpensive, yet efficient route to aromatic CC bond formations since transition metal catalysts and impurities can be avoided by using this reaction system. In this article, we focus on the significance of the reaction conditions (e.g. bases and promoters), which allow this type of reaction to proceed smoothly. Substrate scope limitations and challenges, as well as mechanistic discussion are also included.